2013
DOI: 10.3389/fphys.2013.00251
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptors mediate lung cancer growth

Abstract: Ion channels modulate ion flux across cell membranes, activate signal transduction pathways, and influence cellular transport-vital biological functions that are inexorably linked to cellular processes that go awry during carcinogenesis. Indeed, deregulation of ion channel function has been implicated in cancer-related phenomena such as unrestrained cell proliferation and apoptotic evasion. As the prototype for ligand-gated ion channels, nicotinic acetylcholine receptors (nAChRs) have been extensively studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 59 publications
1
70
1
1
Order By: Relevance
“…Studies by Gardner et al also suggest a role for α3, α4 and α5 containing heteromeric receptors as shown by antagonist and shRNA studies [42]. Implication of a role for α5 receptors in lung cancer growth is also consistent with the reports that polymorphisms in the α3, α5, β4 nAChR gene locus are associated with increased risk of lung cancer [52].…”
Section: Nicotinic Signaling In Lung Cancersupporting
confidence: 64%
“…Studies by Gardner et al also suggest a role for α3, α4 and α5 containing heteromeric receptors as shown by antagonist and shRNA studies [42]. Implication of a role for α5 receptors in lung cancer growth is also consistent with the reports that polymorphisms in the α3, α5, β4 nAChR gene locus are associated with increased risk of lung cancer [52].…”
Section: Nicotinic Signaling In Lung Cancersupporting
confidence: 64%
“…Targeted channels are in color. related nAChRs impairs viability of small cell lung carcinoma cells (SCLC) in vitro (Improgo et al, 2013). Relatively ample evidence is available regrading NSCLC cells, especially involving the ␣7 subunit (e.g., Lam et al, 2007;Grozio et al, 2008;Paleari et al, 2009).…”
Section: Ion Channel Expression and Functional Role In Cancermentioning
confidence: 99%
“…It has been shown that nicotine can promote the growth and metastasis of solid tumors and increase chemotherapeutic resistance by inducing cell proliferation, invasion, angiogenesis and evasion of apoptosis [10][11][12]. These effects are due to the activation of PI3K/AKT, ERK 1/2, MAPK, MEK, NFkB, ␤-arrestin-1, Scr kinase, RbRaf-1 pathways and Bcl-2 family members induced by nicotine [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 97%